Sistema integrado de diagnose e recomendação (DRIS) na cultura do tomateiro em cultivo protegido - Scucuglia, César Lopes (2012)
The cultivation of tomato in greenhouse is present in several regions of Paraná State, it is an option of income for family farmers, and small areas using family labor, in addition to monitoring weather conditions. One of the most important factors for successful cultivation of tomatoes is plant nutrition, however, because of the peculiarities observed in the greenhouse, the forms of interpretation of results of analyzes of soil or foliar nutrients that are made in isolation, is shown conflicting results when using the traditional methods of recommendation. The integrated diagnosis and recommendation (DRIS) has shown satisfactory results in different cultures by examining the interaction between nutrients. In the cultivation of tomato in greenhouse studies are lacking regarding the use of DRIS in this way, this study aimed to establish DRIS norms for growing tomatoes in greenhouses, by studying some of the major nutrients and the interactions between them influencing production. Was used results of chemical analysis of sheets for the nutrients N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn in the yield of 61 greenhouses covered with plastic, with tomato crops, comprising a total area covered implanted with the tomato crop of 24,436 m2 or 2.44 ha. The greenhouses were planted with hybrids, Colibri, Pizzadoro, Max and Deborah Granadero. Samples were collected from April to December of 2010, in greenhouses of the counties of Barra do Jacare, Cambara, Joaquim Tavora, Santo Antonio da Platina and Siqueira Campos, located in the North of Paraná Pioneer. For the formation of the database were used five levels of production, 6, 7, 8, 9 and 10 kg planta-1, with the establishment of binary relationships between all the nutrients studied in all samples. With this information, calculate the mean, standard deviation and variance for each concentration of nutrients, but also for relations between them, in each sub-population. 55 relationships were maintained, which showed the highest ratio in the variance between sub-populations. We calculated the nutritional content of each nutrient and the nutrient balance index (NBI) of each production level. Defined thus the production of 8 kg plant-1 as an index to be used because it presented the best correlation between the NBI and the productions analyzed, and the DRIS norms developed using this pattern of production. In samples that were less than 6 output kg planta-1 was the marked deficiency of K and B, and P, Cu, Mn and Zn on a smaller scale and excess Mg, N and P. In the establishment of DRIS norms when compared to existing standards recommended in the study. It was observed that there were no difference for the nutrients P, K, Ca, Mg and S, the copper content was above the standards, N, Fe and Mn were below the standard and nutrients Zn and B had an amplitude differentiated between the maximum and minimum levels accepted as the norm ideals between DRIS and established standards.